Improved FMEA Methods for Proactive Healthcare Risk Analysis - Liu, Hu-Chen.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book offers an in-depth and systematic introduction to improved failure mode and effects analysis (FMEA) methods for proactive healthcare risk analysis. Healthcare risk management has become an increasingly important issue for hospitals and managers. As a prospective reliability analysis technique, FMEA has been widely used for identifying and eliminating known and potential failures in systems, designs, products or services. However, the traditional FMEA has a number of weaknesses when applied to healthcare risk management. This book provides valuable insights into useful FMEA methods and practical examples that can be considered when applying FMEA to enhance the reliability and safety of the healthcare system. This book is very interesting for practitioners and academics working in the fields of healthcare risk management, quality management, operational research, and management science and engineerin. It can be considered as the guiding document for how a healthcare organization proactively identifies, manages and mitigates the risk of patient harm. This book also serves as a valuable reference for postgraduate and senior undergraduate students.
Healthcare risk management -- FMEA in healthcare: A literature review -- FMEA with cloud model and hierarchical TOPSIS method -- FMEA using interval 2-tuple hybrid weighted distance measure -- FMEA using interval 2-tuple linguistic GRA method -- FMEA based on fuzzy set theory and MULTIMOORA method -- FMEA with interval-valued intuitionistic fuzzy hybrid MCDM approach -- FMEA using combination weighting and fuzzy VIKOR method -- FMEA using interval-valued intuitionistic fuzzy sets and MABAC method -- FMEA based on cluster analysis and prospect theory -- FMEA using interval 2-tuple linguistic variables and ELECTRE method -- FMEA using cloud model theory and PROMETHEE method -- FMEA using hesitant 2-tuple linguistic term sets and QUALIFLEX method.
Keywords: Security systems; Operations research; Health services administration; Electronic data processing -- Management; Security Science and Technology; Operations Research and Decision Theory; Health Care Management; IT Operations